Power of a Quotient

When we encounter an expression with a quotient (or division) inside parentheses and the entire expression is raised to a certain exponent, we can take the exponent and apply it to each of the terms in the expression.
Let's not forget to maintain the fraction bar between the terms.
Formula of the property:
(ab)n=anbn(\frac {a}{b})^n=\frac {a^n}{b^n}
This property is also relevant to algebraic expressions.

Suggested Topics to Practice in Advance

  1. Multiplying Exponents with the Same Base
  2. Division of Exponents with the Same Base
  3. Exponent of a Multiplication

Practice Powers of a Fraction

Examples with solutions for Powers of a Fraction

Exercise #1

Insert the corresponding expression:

(23)a= \left(\frac{2}{3}\right)^a=

Video Solution

Step-by-Step Solution

Let's determine the corresponding expression for (23)a\left(\frac{2}{3}\right)^a:

We apply the property of exponentiation for fractions, which states:
(xy)n=xnyn\left(\frac{x}{y}\right)^n = \frac{x^n}{y^n}.

Substituting x=2x = 2, y=3y = 3, and n=an = a, we have:

(23)a=2a3a\left(\frac{2}{3}\right)^a = \frac{2^a}{3^a}.

Therefore, the correct expression is 2a3a \frac{2^a}{3^a} .

Assessing the possible choices:

  • Choice 1: 23a \frac{2}{3^a} - This is incorrect as it does not raise the numerator to aa.
  • Choice 2: 2a3a \frac{2a}{3a} - This is incorrect as it misuses the exponent rule.
  • Choice 3: 2a3a \frac{2^a}{3^a} - This is correct, as it follows the exponentiation property.
  • Choice 4: 2a3 \frac{2^a}{3} - This is incorrect as it does not raise the denominator to aa.

Thus, the correct choice is Choice 3: 2a3a \frac{2^a}{3^a} .

Answer

2a3a \frac{2^a}{3^a}

Exercise #2

Insert the corresponding expression:

(1013)8= \left(\frac{10}{13}\right)^8=

Video Solution

Step-by-Step Solution

The fraction 1013\frac{10}{13} raised to the power of 8 can be expressed by applying the power to both the numerator and the denominator based on the rule for powers of a fraction:

(1013)8=108138 \left(\frac{10}{13}\right)^8 = \frac{10^8}{13^8}

To solve for the given expression, we use the formula (ab)n=anbn\left(\frac{a}{b}\right)^n = \frac{a^n}{b^n}. This means that the fraction power rule allows us to take each component of the fraction and raise it to the required power:

  • Step 1: Apply the power of 8 to the numerator: 10810^8.
  • Step 2: Apply the power of 8 to the denominator: 13813^8.
  • Step 3: Combine both into a single fraction: 108138\frac{10^8}{13^8}.

Thus, the expression (1013)8\left(\frac{10}{13}\right)^8 simplifies to 108138\frac{10^8}{13^8}.

Therefore, the correct answer from the choices provided is 108138\frac{10^8}{13^8}, corresponding to choice 3.

Answer

108138 \frac{10^8}{13^8}

Exercise #3

Insert the corresponding expression:

(37)6= \left(\frac{3}{7}\right)^6=

Video Solution

Step-by-Step Solution

The problem asks us to express (37)6 \left(\frac{3}{7}\right)^6 in another form. To solve this, we apply the exponent rule for fractions: (ab)n=anbn\left(\frac{a}{b}\right)^n = \frac{a^n}{b^n}.

  • First, identify the numerator and the denominator in the fraction 37 \frac{3}{7} .
  • We have a=3 a = 3 and b=7 b = 7 .
  • According to the exponent rule, raise both the numerator and the denominator separately to the power of 6:

(37)6=3676 \left(\frac{3}{7}\right)^6 = \frac{3^6}{7^6}

This signifies that each component of the fraction is raised to the power of 6.

To verify, we compare our result with the given choices:

  • Option 1: 376 \frac{3}{7^6} does not apply the exponent to the "3".
  • Option 2: 3676 \frac{3^6}{7^6} , matches our derived expression.
  • Option 3: 367 \frac{3^6}{7} does not apply the exponent to the "7".
  • Option 4: 6×(37)5 6\times\left(\frac{3}{7}\right)^5 changes the power on the entire fraction and multiplies by 6, which is incorrect based on our interpretation.

Therefore, the solution to the problem is 3676 \frac{3^6}{7^6} , which corresponds to choice 2.

Answer

3676 \frac{3^6}{7^6}

Exercise #4

Insert the corresponding expression:

(ab)9= \left(\frac{a}{b}\right)^9=

Video Solution

Step-by-Step Solution

The problem asks us to express (ab)9\left(\frac{a}{b}\right)^9 using exponent rules. We will use the rule for the power of a fraction, which states:

(ab)n=anbn\left(\frac{a}{b}\right)^n = \frac{a^n}{b^n}

Applying this rule, we get:

(ab)9=a9b9\left(\frac{a}{b}\right)^9 = \frac{a^9}{b^9}

This method ensures that the exponent 99 is applied to both the numerator and the denominator of the fraction.

Therefore, the solution to the problem is a9b9\frac{a^9}{b^9}.

Answer

a9b9 \frac{a^9}{b^9}

Exercise #5

Insert the corresponding expression:

(1013)4= \left(\frac{10}{13}\right)^{-4}=

Video Solution

Step-by-Step Solution

To solve the expression (1013)4\left(\frac{10}{13}\right)^{-4}, we start by applying the rule for dividing exponents is:

104134\frac{10^{-4}}{13^{-4}}, which maintains the negative exponent but as separate components of fraction resulting in the same value.

Consequently, the expression (1013)4\left(\frac{10}{13}\right)^{-4} equates to 104134\frac{10^{-4}}{13^{-4}}.

By comparing this with the presented choices, we identify that option (2):

104134 \frac{10^{-4}}{13^{-4}}

matches correctly with our conversion of the original expression.

Therefore, the correct expression is 104134\frac{10^{-4}}{13^{-4}}.

Answer

104134 \frac{10^{-4}}{13^{-4}}

Exercise #6

Insert the corresponding expression:

(5y)7= \left(\frac{5}{y}\right)^7=

Video Solution

Step-by-Step Solution

To solve this problem and transform the expression (5y)7\left(\frac{5}{y}\right)^7, we need to utilize the exponent rule for powers of fractions:

  • Step 1: Recognize that the expression (5y)7\left(\frac{5}{y}\right)^7 involves both the numerator 5 and the denominator yy.
  • Step 2: According to the exponent rule (ab)n=anbn\left(\frac{a}{b}\right)^n = \frac{a^n}{b^n}, we can apply the exponent of 7 to both the numerator and the denominator.
  • Step 3: Applying this rule gives us 57y7\frac{5^7}{y^7}. This step distributes the power to each component of the fraction, preserving the structure of the expression.

Thus, the simplified form of the expression (5y)7\left(\frac{5}{y}\right)^7 is 57y7\frac{5^7}{y^7}.

This matches choice 3 from the provided options.

Answer

57y7 \frac{5^7}{y^7}

Exercise #7

Insert the corresponding expression:

(b5)4= \left(\frac{b}{5}\right)^4=

Video Solution

Step-by-Step Solution

To solve this problem, we'll apply the exponent rule for fractions:

  • Step 1: Identify the fraction b5\frac{b}{5} and the power 44.
  • Step 2: Apply the exponent to both the numerator and the denominator, as per the formula.
  • Step 3: Use the rule (b5)4=b454 \left(\frac{b}{5}\right)^4 = \frac{b^4}{5^4} .

Now, let's work through the application:
Step 1: We have the base fraction b5\frac{b}{5} and exponent 44.
Step 2: According to the exponent rule, (ab)n=anbn \left(\frac{a}{b}\right)^n = \frac{a^n}{b^n} , apply the exponent 44 to both bb and 55.
Step 3: This results in the expression b454\frac{b^4}{5^4}.

Therefore, the expression (b5)4 \left(\frac{b}{5}\right)^4 simplifies to b454 \frac{b^4}{5^4} .

Answer

b454 \frac{b^4}{5^4}

Exercise #8

Insert the corresponding expression:

(58)9= \left(\frac{5}{8}\right)^9=

Video Solution

Step-by-Step Solution

To solve this problem, we'll apply the rule for raising a fraction to a power:

Using the formula (ab)n=anbn\left(\frac{a}{b}\right)^n = \frac{a^n}{b^n}, we can express (58)9\left(\frac{5}{8}\right)^9 as follows:

Step 1: Identify the base and exponent in (58)9\left(\frac{5}{8}\right)^9. Here, a=5a = 5, b=8b = 8, and n=9n = 9.

Step 2: Apply the exponentiation rule:
(58)9=5989\left(\frac{5}{8}\right)^9 = \frac{5^9}{8^9}.

Therefore, the original expression simplifies to 5989\frac{5^9}{8^9}.

As a result, the correct rewritten form of (58)9\left(\frac{5}{8}\right)^9 is 5989\frac{5^9}{8^9}.

Answer

5989 \frac{5^9}{8^9}

Exercise #9

Insert the corresponding expression:

(2021)4= \left(\frac{20}{21}\right)^4=

Video Solution

Step-by-Step Solution

To solve this problem, we'll follow these steps:

  • Identify the given expression which is (2021)4\left(\frac{20}{21}\right)^4.

  • Apply the exponentiation rule for fractions: (ab)n=anbn\left(\frac{a}{b}\right)^n = \frac{a^n}{b^n}.

  • Calculate 20420^4 and 21421^4 and place them as the numerator and denominator, respectively.

Now, let's work through each step:
Step 1: We begin with the expression (2021)4\left(\frac{20}{21}\right)^4.
Step 2: Using the power of a fraction rule, we have (2021)4=204214\left(\frac{20}{21}\right)^4 = \frac{20^4}{21^4}.

Therefore, the corresponding simplified expression is 204214\frac{20^4}{21^4}.

Answer

204214 \frac{20^4}{21^4}

Exercise #10

Insert the corresponding expression:

(1319)7= \left(\frac{13}{19}\right)^7=

Video Solution

Step-by-Step Solution

To solve this problem, we'll follow these steps:

  • Step 1: Identify the given expression (1319)7\left(\frac{13}{19}\right)^7.
  • Step 2: Apply the exponent rule for fractions: (ab)n=anbn\left(\frac{a}{b}\right)^n = \frac{a^n}{b^n}.
  • Step 3: Perform the calculation by raising both the numerator and the denominator to the power of 7.

Now, let's work through each step:
Step 1: The expression provided is (1319)7\left(\frac{13}{19}\right)^7, which is a fraction raised to an exponent.
Step 2: Using the exponentiation rule for fractions: (ab)n\left(\frac{a}{b}\right)^n is equivalent to anbn\frac{a^n}{b^n}.
Step 3: Applying this rule, we express (1319)7\left(\frac{13}{19}\right)^7 as 137197\frac{13^7}{19^7}.

Therefore, the solution to the problem is 137197\frac{13^7}{19^7}, which corresponds to choice 1.

Answer

137197 \frac{13^7}{19^7}

Exercise #11

Insert the corresponding expression:

(29)7= \left(\frac{2}{9}\right)^7=

Video Solution

Step-by-Step Solution

To solve this problem, we'll use the rule for powers of a fraction, which states that (ab)n=anbn\left(\frac{a}{b}\right)^n = \frac{a^n}{b^n}.

Given the expression (29)7\left(\frac{2}{9}\right)^7, we apply this exponent rule:

(29)7=2797\left(\frac{2}{9}\right)^7 = \frac{2^7}{9^7}

This means we raise the numerator, 2, to the power of 7, and the denominator, 9, also to the power of 7.

The matching choice in the given options is:

  • Choice 1: 2797\frac{2^7}{9^7}

Therefore, the solution to the problem is 2797\frac{2^7}{9^7}.

Answer

2797 \frac{2^7}{9^7}

Exercise #12

Insert the corresponding expression:

(12)2= \left(\frac{1}{2}\right)^2=

Video Solution

Step-by-Step Solution

To solve this problem, we must square the fraction (12)\left(\frac{1}{2}\right). The exponent rule for fractions states that when you raise a fraction (ab)\left(\frac{a}{b}\right) to the power of nn, it becomes anbn\frac{a^n}{b^n}.

Here, in the fraction (12)\left(\frac{1}{2}\right), we identify the numerator a=1a = 1 and the denominator b=2b = 2, with the exponent n=2n = 2.

Applying the formula, we calculate the result:
(12)2=1222 \left(\frac{1}{2}\right)^2 = \frac{1^2}{2^2}

Therefore, the expression that corresponds to (12)2\left(\frac{1}{2}\right)^2 is 1222\frac{1^2}{2^2}, which directly matches the given choice.

The correct choice from the answer options is:

  • Choice 3: 1222\frac{1^2}{2^2}

Therefore, the solution to the problem is 1222\frac{1^2}{2^2}.

Answer

1222 \frac{1^2}{2^2}

Exercise #13

Insert the corresponding expression:

(15)3= \left(\frac{1}{5}\right)^3=

Video Solution

Step-by-Step Solution

To solve this problem, we need to simplify the expression (15)3 \left(\frac{1}{5}\right)^3 using the exponent rules for fractions:

  • Step 1: Identify the base and the exponent. Here, the base is 15 \frac{1}{5} and the exponent is 3 3 .
  • Step 2: Apply the rule for raising a fraction to a power. The rule states that (ab)n=anbn \left(\frac{a}{b}\right)^n = \frac{a^n}{b^n} .
  • Step 3: Apply the exponent to both the numerator and the denominator:

Thus, (15)3=1353 \left(\frac{1}{5}\right)^3 = \frac{1^3}{5^3} .

Therefore, the simplified expression is 1353 \frac{1^3}{5^3} , which corresponds to choice 1 in the provided options.

Answer

1353 \frac{1^3}{5^3}

Exercise #14

Insert the corresponding expression:

(23)2= \left(\frac{2}{3}\right)^2=

Video Solution

Step-by-Step Solution

To solve this problem, we will apply the exponent rule for fractions:

  • Step 1: We are given the expression (23)2\left(\frac{2}{3}\right)^2.
  • Step 2: Apply the fraction exponent rule: (ab)n=anbn\left(\frac{a}{b}\right)^n = \frac{a^n}{b^n}.

Applying this rule to our expression:

(23)2=2232\left(\frac{2}{3}\right)^2 = \frac{2^2}{3^2}.

Calculating further would give:

2232=49 \frac{2^2}{3^2} = \frac{4}{9} .

However, the question asks to only match the expression, which is 2232\frac{2^2}{3^2}.

The correct choice from the given options is 2232\frac{2^2}{3^2}.

This matches Choice 3 in the provided multiple choices.

Answer

2232 \frac{2^2}{3^2}

Exercise #15

Insert the corresponding expression:

(xy)8= \left(\frac{x}{y}\right)^8=

Video Solution

Step-by-Step Solution

To solve this problem, we will apply the power of a fraction rule:

Step 1: Recognize that we are asked to simplify (xy)8\left(\frac{x}{y}\right)^8.

Step 2: Apply the power of a fraction rule, which states:

  • (ab)n=anbn\left(\frac{a}{b}\right)^n = \frac{a^n}{b^n}

Step 3: Use this formula to obtain:

(xy)8=x8y8\left(\frac{x}{y}\right)^8 = \frac{x^8}{y^8}

Therefore, the simplified expression of (xy)8\left(\frac{x}{y}\right)^8 is x8y8\frac{x^8}{y^8}.

The correct choice from the given options is:

x8y8 \frac{x^8}{y^8}

Answer

x8y8 \frac{x^8}{y^8}